Development of Recycled Polypropylene Plastic Fibres to Reinforce Concrete - Yin, Shi (Springer Singapore : Imprint: Springer, 2017)
This book outlines a methodology for producing macro recycled polypropylene (PP) fibres with optimal mechanical properties and illustrates the reinforcing effects of recycled PP fibres in concrete. It describes the great potential of using these fibres in concrete applications such as footpaths and precast elements. Further, it sheds new light on the environmental impacts of using recycled PP fibres, which are evaluated by means of cradle to gate life cycle assessment based on the Australian context. The use of recycled PP fibre not only helps reduce consumption of virgin materials like steel or plastic but also provides an attractive avenue for recycling plastic waste. The book will appeal to engineers, governments, and solid waste planners, and offers a valuable reference for the plastic waste recycling and plastic fibre reinforced concrete industries.
Keywords: Materials science.; Building materials.; Structural materials.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books